Individual and mutual effects of diabetes, hypertension, and obesity on acute respiratory distress syndrome mortality rates in clinical patients: a multicentre study - de Araújo, Márcio Flávio Moura; Monteiro, Flávia Paula Magalhães; de Araújo, Thiago Moura; Lira Neto, José Cláudio Garcia; Santos, Lívia Fernanda Siqueira; Rolim, Isaura Letícia Tavares Palmeira; Santos, Floriacy Stabnow; Pascoal, Livia Maia; Costa, Ana Cristina Pereira de Jesus; Santos Neto, Marcelino (Frontiers in Public Health, 2023)
Patients with comorbidities are more vulnerable to severe clinical cases of acute respiratory distress syndrome (ARDS) and COVID-19 require complex health care. To analyse the association between the individual and combined effects of diabetes, hypertension, and obesity on ARDS mortality rates among patients receiving clinical care. A multicentre study encompassing retrospective data analysis and conducted with 21,121 patients from 6,723 health services across Brazil, during the 2020-2022 time period. The sample group consisted of clinical patients of both sexes and different age groups who received clinical care and showed at least one comorbidity. The data collected were analysed using binary logistic regressions and the Chi-square test. The overall mortality rate was 38.7%, with a higher predominance among males (p<0.001), mixed-race individuals (p<0.001), and older adults (p<0.001). The main comorbidity variables associated with and leading to death from ARDS were arterial hypertension (p<0.001), diabetes mellitus (p<0.001), diabetes mellitus and arterial hypertension (p<0.001), cardiovascular diseases (p<0.001), and obesity (p<0.001). Both the patients who progressed to recovery (48.4%) and to death (20.5%) presented only one comorbidity (χ² (1,749) =8, p<0.001), respectively). The isolated comorbidities with the greatest impact on death outcomes were diabetes (95% CI 2.48-3.05, p<0.001), followed by obesity (95% CI 1.85-2.41, p<0.001) and hypertension (95% CI 1.05-1.22, p<0.001), even after adjusting for sex and number of simultaneous comorbidities. Diabetes and obesity, as isolated conditions, had a greater influence on the number of deaths of clinical patients with ARDS compared to those with mutual diagnosis of diabetes, hypertension, and obesity.